3D Printing Nanoscale Bioactive Glass Scaffolds Enhance Osteoblast Migration and Extramembranous Osteogenesis through Stimulating Immunomodulation. Issue 16 (27th June 2018) - Zhao, Fujian; Xie, Weihan; Zhang, Wen; Fu, Xiaoling; Gao, Wendong; Lei, Bo; Chen, Xiaofeng
Abstract: Bioactive glass (BG) can repair bone defects, however, it is not clear whether BG has the ability for bone augmentation without making any bone defect. Unlike the intramembranous osteogenesis in bone defect repair, the extramembranous osteogenesis occurs outside the cortical bone and the osteoprogenitor cells show the reversed migration. Herein, nanoscale bioactive glass scaffolds (BGSs) are fabricated, and their role and immunomodulation‐related mechanism in the extramembranous osteogenesis are investigated. The in vitro migration and differentiation of calvaria preosteoblasts are studied by culturing with peripheral macrophage‐conditioned medium after stimulating with BGSs. The results indicate that the proinflammatory environment significantly promotes preosteoblast migration, but has limited effect on osteogenic differentiation. However, the anti‐inflammatory environment and BGSs significantly increase the osteogenic differentiation of preosteoblasts. The in vivo extramembranous osteogenesis evaluation shows that the active osteogenesis is observed near the skull. The osteoblasts derived from the reverse migration of cranial cells can be confirmed by comparing with the scaffolds implanted in back subcutaneous which is just colonized by fibrous tissue. This study may bring a fresh perspective for BG in bone regeneration and explore the osteogenic immunomodulation of peripheral macrophages in a nonosteogenic environment. Abstract : Bioactive glass is generally considered to be a bone repair material to repair bone defects. Herein, a bioactive glass scaffold is observed to have the ability of forming new bone outside the cortical bone without making any bone defect, which is named as "extramembranous osteogenesis." In addition, the migration and differentiation of osteoblasts forming cortical bone are significantly influenced by the macrophage polarization.